Early Ordovician (Skullrockian) Trilobites of the Antiklinalbugt Formation, Northeast Greenland, and their Biostratigraphic Significance. (September 2014) - McCobb, Lucy M. E.; Boyce, W. Douglas; Knight, Ian; Stouge, Svend
Abstract : The Antiklinalbugt Formation of northeast Greenland comprises peritidal to subtidal carbonate sediments, deposited in shallow shelf settings during an early Tremadocian transgressive-regressive megacycle. The succession of shales and microbial, muddy and grainy limestone, with minor dolostone at the base and top, terminates at the cryptic Fimbulfjeld disconformity. The formation has yielded trilobites collected on Ella Ø, Albert Heim Bjerge, and Kap Weber by C. Poulsen (1920s and 1930s), J. W. Cowie and P. J. Adams (1950s), and during recent field studies in 2000 and 2001. The fauna includes dimeropygids Tulepyge cowiei and T. tesella n. spp., hystricurids Millardicurus and Hystricurus, and several species of Symphysurina. Micragnostus chiushuensis (Kobayashi, 1931) is rare, as are Chasbellus sp., Clelandia sp., and Lunacrania ?. The presence of several Symphysurina species places the Antiklinalbugt Formation within the Symphysurina Zone. Chasbellus indicates the upper (lower Ordovician) part of the Symphysurina Zone for the lower upper Antiklinalbugt Formation. Conodonts place the middle lower formation in the Cordylodus intermedius conodont Biozone, the lower upper part in the Cordylodus angulatus conodont Biozone and the uppermost part in the Rossodus manitouensis conodont Biozone. This combined fauna is characteristic of the upper Skullrockian Stage of the Ibexian Series, with the lower part of the Antiklinalbugt Formation lying within the uppermost Cambrian of North America, and the upper part within the lower Ordovician. The entire formation lies within the global Tremadocian Stage of the early Ordovician.